Ferroelectric [HfO 2 /ZrO 2 ] Superlattices with Enhanced Polarization, Tailored Coercive Field, and Improved High Temperature Reliability - Lehninger, David; Prabhu, Aditya; Sünbül, Ayse; Ali, Tarek; Schöne, Fred; Kämpfe, Thomas; Biedermann, Kati; Roy, Lisa; Seidel, Konrad; Lederer, Maximilian; Eng, Lukas M. (Advanced Physics Research, 2023)
Modern microelectronic systems and applications demand an every increasing amount of non‐volatile memories that are fast, reliable, and consume little power. Memory concepts based on ferroelectric HfO 2 like the ferroelectric field effect transistor (FeFET) and the ferroelectric random access memory (FeRAM) are promising to satisfy these requirements. As a consequence, continuing high attention is given to improve the ferroelectric properties and the reliability characteristics of the ferroelectric HfO 2 films – for instance by using different dopant elements, dopant concentrations, and film thicknesses. Superlattices (i.e., a periodic structure of two materials stacked upon each other) are a promising alternative approach. Herein, [HfO 2 /ZrO 2 ] superlattices of various sublayer thicknesses and a constant total thickness of 10 nm are embedded into metal‐ferroelectric‐metal (MFM) capacitors and then electrically as well as structurally characterized with special focus on remanent polarization, coercive field, endurance, and high temperature reliability. Compared to a 10 nm (Hf,Zr)O 2 solid solution reference film, the use of superlattice stacks significantly improves the above mentioned parameters. In addition, most of these parameters depend on the sublayer thickness, which allows, for instance, tailoring the coercive field of the whole device.